Factors Associated With the Health and Economic Effects of the COVID-19 Pandemic in the Peruvian Textile Sector, 2020–2021 - Arroyo-Laguna, Juan; Timaná-Ruíz, Raúl (Frontiers in Sociology, 2022)
The article identifies the factors associated with the health and economic effects of the COVID-19 pandemic on people working in the textile industry of Lima, Peru, during 2021. The study was conducted in Peru's largest textile emporium, so-called Gamarra. The study design is observational and cross-sectional, with two models with two temporal samples for the first and second waves of the COVID-19 pandemic. The first model measures the chance of getting sick from COVID-19. The second model measures the economic impact by the variations in incomes. Inferential statistics are employed, using the chi-square test. The p-value (p < 0.05) is evaluated to decide the statistical significance of the variables. Of 820 workers included, 48% work in street trading, 45% are ≤ 35 years of age and 15% are foreign migrants. Logistic regression analysis for the first model reveals an association between infection by a family member, people breaking quarantine, foreign nationality, not having hygienic services and having a chronic disease, with the highest probability of COVID-19 infection. Regarding economic impact, an association is found between educational level, being ≥45 years of age and infection of a family member, with a greater probability of variation in income.